1991
DOI: 10.1161/01.cir.83.5.1605
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic detection of coronary artery disease during dobutamine infusion.

Abstract: Echocardiography combined with dobutamine infusion is a safe and accurate method for detecting coronary artery disease and for predicting the extent of disease in those who have localized rest wall motion abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
202
3
6

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 644 publications
(219 citation statements)
references
References 27 publications
6
202
3
6
Order By: Relevance
“…16) When segments of the left ventricle were divided according to the territories supplied by each coronary artery, 9 segments that were supplied by the left anterior descending artery were assigned to the anterior infarct zone; basal and mid anterior septum (at parasternal long axis), mid septum, apical septum, apicolateral (at four chamber), inferoapical, anteroapical, and mid and basal anterior (at two chamber). 17) The wall motion score index (WMSI) was calculated under the basal condition and at the two dobutamine dose levels and defined as the sum of the individual wall motion scores divided by the respective number of the measured segments. 10) Inadequately visualized segments were not scored, and if more than 2 segments of the infarct zone or 4 or more of all 16 segments were not visualized, the study was considered inadequate for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…16) When segments of the left ventricle were divided according to the territories supplied by each coronary artery, 9 segments that were supplied by the left anterior descending artery were assigned to the anterior infarct zone; basal and mid anterior septum (at parasternal long axis), mid septum, apical septum, apicolateral (at four chamber), inferoapical, anteroapical, and mid and basal anterior (at two chamber). 17) The wall motion score index (WMSI) was calculated under the basal condition and at the two dobutamine dose levels and defined as the sum of the individual wall motion scores divided by the respective number of the measured segments. 10) Inadequately visualized segments were not scored, and if more than 2 segments of the infarct zone or 4 or more of all 16 segments were not visualized, the study was considered inadequate for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated to be a safe and useful method for detecting CAD. [11][12][13] However, results were obtained in studies in which patient populations were predominantly men, who have a higher prevalence of CAD than women; in addition, scant information is available in women. Studies have reported on heterogeneous populations since patients with previous myocardial infarction or known CAD had been included.…”
Section: Discussionmentioning
confidence: 99%
“…Dobutamine stress echocardiography (DOBE) is increasingly used for detection of CAD, 11,12 but its diagnostic accuracy has not been defined in women.…”
Section: Introductionmentioning
confidence: 99%
“…Dobutamine stress has now emerged as the best alternative to exercise with very similar diagnostic accuracy [17][18][19]. Dobutamine is a catecholamine with selective beta-1 adrenoreceptor agonist activity and a relatively weak action on alpha and beta-2 adrenoreceptors.…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 99%